Diagnostic accuracy of transvaginal sonography for detecting parametrial involvement in women with deep endometriosis: systematic review and meta‐analysis. (1st November 2021) - Guerriero, S.; Martinez, L.; Gomez, I.; Pascual, M. A.; Ajossa, S.; Pagliuca, M.; Alcázar, J. L.
ABSTRACT: Objective: To evaluate the accuracy of transvaginal sonography (TVS) for detecting parametrial deep endometriosis, using laparoscopy as the reference standard. Methods: A search was performed in PubMed/MEDLINE and Web of Science for studies evaluating TVS for detecting parametrial involvement in women with suspected deep endometriosis, as compared with laparoscopy, from January 2000 to December 2020. The Quality Assessment of Diagnostic Accuracy Studies‐2 (QUADAS‐2) tool was used to evaluate the quality of the studies. Pooled sensitivity, specificity and positive and negative likelihood ratios for TVS in the detection of parametrial deep endometriosis were calculated, and the post‐test probability of parametrial deep endometriosis following a positive or negative test was determined. Results: The search identified 134 citations. Four studies, comprising 560 patients, were included in the analysis. The mean prevalence of parametrial deep endometriosis at surgery was 18%. Overall, the pooled estimated sensitivity, specificity and positive and negative likelihood ratios of TVS in the detection of parametrial deep endometriosis were 31% (95% CI, 10–64%), 98% (95% CI, 95–99%), 18.5 (95% CI, 8.8–38.9) and 0.70 (95% CI, 0.46–1.06), respectively. The diagnostic odds ratio was 26 (95% CI, 10–68). Heterogeneity was high. Visualization of a lesion suspected to be parametrial deep endometriosis on TVS increased significantly the post‐test probability of parametrial deep endometriosis. Conclusion: TVS has high specificity but low sensitivity for the detection of parametrial deep endometriosis. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.